RHEED analysis of the oxidized M′2M″xXyene sheets by ablated plasma thrust method in pulsed laser deposition chamber - D. Parajuli (AIP Publishing LLC, 2021)
M′2M″xXyene (M′ and M″ are the early transitional metals and X is carbide with x = 1 for y = 2 and x = 2 for y = 3) are the ordered double transitional metal layered carbides derived from their parent MAX phases M′2M″xAlXyene by a wet chemical etching method. Their oxides are predicted to have topological properties for which they should be annealed at around 800 °C in an oxygen background. This paper includes the new ablated plasma thrust method for the ionization and adsorption of oxygen on the M′2M″xXyene substrate in the pulsed laser deposition chamber. We have found that the background pressure has a negative effect and the substrate temperature has a positive effect on plume expansion. The density profile of the background gas is highly affected by deposition temperature. Similarly, it is found that the density of plasma generated by longer wavelengths is not affected significantly due to the inverse bremsstrahlung process. A shorter wavelength produces the bremsstrahlung process as photoionization takes place. At a certain time (200 ns), the pressure of background gas and plasma pressure are equal (snow-plogh effect) so that all the wavelengths then produce electrons (highest for shorter wavelengths), thereby increasing its density. The energy necessary for the oxidation of the substrate is provided by the energy of the ablated species. The adsorption is assured by the reflective high electron energy diffraction technique, and it is found that the ambient gas pressures p = 0.1 mbar and 0.2 mbar are appropriate for the adsorption process. The obtained M′2M″xXyene oxides can be used for their topological test.